THE LEAN 4.0 WORKSHOP: AN OVERVIEW - Pratama, Aditya Tirta; Sofianti, Tanika Dewi; Saraswati, Triarti; Simorangkir, Niklas Parlindungan; Kurniawan, Ivan (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
In today's industrial landscape, companies must enhance operational efficiency, productivity, and sustainability while integrating traditional Lean manufacturing principles with Industry 4.0 technologies like IoT, AI, and data analytics. Despite the potential benefits, there is a significant gap in understanding and implementing Lean 4.0. The Lean 4.0 Workshop aims to provide a comprehensive and practical understanding of how Lean principles can be integrated with Industry 4.0 technologies to enhance industrial performance and sustainability. The event, held at Pusat Industri Digital (PIDI) 4.0, attracted representatives from many notable companies. This paper focuses on the benefits this event provides to the community. The workshop presentations disseminate ongoing research as well as theoretical and practical concepts in various areas of Lean 4.0. The exhibition of industrial tools and processes allows participants to become more familiar with advanced technologies and their practical applications. Considering the event's performance, the Lean 4.0 workshop was a success, with over 80 participants showing great interest and actively participating, along with effective and efficient knowledge sharing. Based on the satisfaction survey, 42.9% of respondents were very satisfied with the workshop, and 64.3% found it met their expectations, though not to the fullest extent.